2013
DOI: 10.1002/jcb.24459
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols suppress hydrogen peroxide‐induced oxidative stress in human bone‐marrow derived mesenchymal stem cells

Abstract: Human mesenchymal stem cells (hMSCs) are considered a highly promising candidate cell type for cell-based tissue engineering and regeneration because of their self-renewal and multi-lineage differentiation characteristics. Increased levels of reactive oxygen/nitrogen species (ROS/RNS) are associated with tissue injury and inflammation, impact a number of cellular processes, including cell adhesion, migration, and proliferation, and have been linked to cellular senescence in MSCs, potentially compromising their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 49 publications
2
101
0
Order By: Relevance
“…The ROS that are generated by mitochondrial respiration, including H 2 O 2 , are potentially potent inducers of oxidative damage (27). Therefore, we used exogenous H 2 O 2 as a source of oxidative stress, and exposed WT MSCs to various concentrations of H 2 O 2 for 24 hours to generate a dose-response curve ( Figure E3).…”
Section: Autophagic Protein-depleted Mscs Show Increased Susceptibilimentioning
confidence: 99%
“…The ROS that are generated by mitochondrial respiration, including H 2 O 2 , are potentially potent inducers of oxidative damage (27). Therefore, we used exogenous H 2 O 2 as a source of oxidative stress, and exposed WT MSCs to various concentrations of H 2 O 2 for 24 hours to generate a dose-response curve ( Figure E3).…”
Section: Autophagic Protein-depleted Mscs Show Increased Susceptibilimentioning
confidence: 99%
“…1) MSCs are known as multipotent fibroblast cells that give rise to cells of the skeletal connective tissue including osteoblasts, chondrocytes, and adipocytes. However, their clinical applications are limited in their expandability and differentiation capacity, because oxidative stress from ROS impact a number of cellular processes, including cell adhesion, migration, and proliferation.…”
Section: Protective Effect Of Sinapine Against Hydroxyl Radical-inducmentioning
confidence: 99%
“…1) Because of this, several types of phytophenols have been investigated for the beneficial effects on MSCs, such as flavonoids (quercetin and rutin), 3) lignan (honokiol), 4) coumarin (7,8-dihydroxy coumarin), 5) anthraquinone (emodin), 6) phenolic acid (protocatechuic acid), 7) stilbene (resveratrol), 8) epigallocatechin-3-gallate (EGCG), and curcumin. 1) Our recent studies have demonstrated that a phenolic acid ester (chlorogenic acid) and a phenolic ketone (maclurin) could also effectively protect MSCs from damage induced by hydroxyl radical (·OH), which is the most harmful form of ROS. 9,10) As a special phytophenol, sinapine however contains an N atom in the molecule (Fig.…”
Section: Protective Effect Of Sinapine Against Hydroxyl Radical-inducmentioning
confidence: 99%
“…The selection was based on a high available cell number and stable in vitro trilineage differentiation capacity (data not shown). BMSCs in our bank were harvested from femoral heads as previously described [24]. Briefly, femoral heads were obtained from patients undergoing total hip arthroplasty with Institutional Review Board (IRB) approval (University of Washington and University of Pittsburgh), and bone marrow and bone chips were harvested from the core of the trabecular bone.…”
Section: Bmsc Culturementioning
confidence: 99%